SCREENING AND EVALUATION OF PHARMACOGNOSTIC, PHYTOCHEMICAL AND HEPATOPROTECTIVE ACTIVITY OF JUNIPERUS COMMUNIS LINN. STEMS - MANVI,; GANESH PRASAD GARG, (International Journal of Pharma and Bio Sciences, 2010)
Detailed microscopy of Juniperus communis Linn. stems (J. communis) has been worked up along with the determination of various physico-chemical parameters viz. moisture content, ethanol and water soluble extractives and total, water soluble and acid insoluble ash values. Preliminary phytochemical analysis indicated the presence of glycosides, alkaloids, flavonoids, steroids, triterpenoids and tannins. Further, qualitative TLC fingerprint profiles of petroleum ether, chloroform and ethanol extracts of J. communis were also developed to facilitate proper identification of the plant material. J. communis was evaluated for hepatoprotective activity using carbon tetrachloride (CCl4)- induced hepatic damage in rats. It was concluded that stems possess hepatoprotective activity.